The optimization performance of cross-linked sodium alginate polymer electrolyte bio-membranes in passive direct methanol/ethanol fuel cells - Shaari N.; Zakaria Z.; Kamarudin S.K. (John Wiley and Sons Ltd, 2023)
Binary alloys; Catalyst selectivity; Costs; Crosslinking; Direct ethanol fuel cells (DEFC); Direct methanol fuel cells (DMFC); Electrodes; Ethanol; Ethanol fuels; Gas fuel purification; Hydrogen storage; Membranes; Methanol; Methanol fuels; Platinum alloys; Proton exchange membrane fuel cells (PEMFC); Ruthenium alloys; Sodium; Sodium alginate; Solid electrolytes; Bio membranes; Commercial membranes; Direct methanol fuel cells (DMFCs); Operation performance; Optimum temperature; Polymer electrolyte membranes; Portable applications; Thermal characterization; Polyelectrolytes